Ecology of aerobic anoxygenic phototrophs in aquatic environments - Koblížek, Michal (FEMS microbiology reviews, 2015)
Recognition of the environmental role of photoheterotrophic bacteria has been one of the main themes of aquatic microbiology over the last 15 years. Aside from cyanobacteria and proteorhodopsin-containing bacteria, aerobic anoxygenic phototrophic (AAP) bacteria are the third most numerous group of phototrophic prokaryotes in the ocean. This functional group represents a diverse assembly of species which taxonomically belong to various subgroups of Alpha-, Beta- and Gammaproteobacteria. AAP bacteria are facultative photoheterotrophs which use bacteriochlorophyll-containing reaction centers to harvest light energy. The light-derived energy increases their bacterial growth efficiency, which provides a competitive advantage over heterotrophic species. Thanks to their enzymatic machinery AAP bacteria are active, rapidly growing organisms which contribute significantly to the recycling of organic matter. This chapter summarizes the current knowledge of the ecology of AAP bacteria in aquatic environments, implying their specific role in the microbial loop.
Keywords: Biodiversity; aerobní bakterie; životní prostředí; vodní organismy; Environment; potravní řetězec; biodiverzita; Ecology; Oceans and Seas; bacterial growth; Food Chain; Bacteria, Aerobic; Aquatic Organisms; fototrofní procesy; mikrobiologie vody; ekologie; aquatic food webs; Phototrophic Processes; microbial loop; Water Microbiology; bacteriochlorophyll; oceány a moře; photoheterotrophs